Hubungan Mutu Pelayanan Keperawatan Dengan Kepuasan Pasien di Rumah Sakit Umum Daerah Dr. RM. Djoelham Binjai Tahun 2024 - Ardianto Ardianto (KOLONI, 2024)
A hospital is an integral part of a social and health organization with the function of providing complete (comprehensive) services, curing disease (curative) and preventing disease (preventive) to the community. The quality of nursing services is service to patients that is based on expertise standards for the patient's needs and desires, so that patients can obtain satisfaction which ultimately can increase trust in the hospital. Patient satisfaction can also be interpreted as a consumer attitude, namely several degrees of liking or disliking the service they have experienced. This type of research is an illustrative study using a cross sectional analytical study design. The aim of the research is to determine the relationship between the quality of nursing services and patient satisfaction at the Dr. Regional General Hospital. RM. Djoelham Binjai in 2023. In this research, the sampling technique was carried out by taking 20% ​​of the total population, namely 20% of 150 = 30 people. The results of hypothesis testing to see the relationship between variable 0.05). Conclusion: There is a relationship between the quality of nursing services and patient satisfaction at the Dr. Regional General Hospital. RM. Djoelham Binjai in 2024.